ANALISIS PRODUKTIVITAS BARECORE MENGGUNAKAN METODE OBJECTIVE MATRIX (OMAX) DAN FAULT TREE ANALYSIS (FTA) PADA PT PUNDI ALAM PERKASA - Gris, Favian Devara; Nugroho, Andung Jati (Bhinneka Multidisiplin Journal, 2024)
Productivity is an important factor that supports a company's ability to produce optimal output using available resources. PT. Pundi Alam Perkasa is one of the wood processing industries in Temanggung Regency that has been established since 2011, with the type of production, namely Barecore which is made from albasia wood. In its production process, PT. Pundi Alam Perkasa uses enormous resources, both human resources and raw materials. However, the barecore production target given by the company of 37,500 units or in cubic size of 1,451.062 M3 per month has not been met. Based on the results of the study, the productivity level of PT. Pundi Alam Perkasa is very fluctuating because the average production for the last 6 months, namely from April - September 2023, was 1428.15 M3, which means that the production target has not been met. The criteria used in this study are raw material productivity, labor productivity, effective working hour productivity, machine working hour productivity, and effective production productivity. The highest productivity value was achieved in August 2023 with a score of 740 because four criteria were above average. While the lowest value was recorded in April 2023 with a productivity value of only 309